2014
DOI: 10.1016/j.finel.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Topology synthesis of multi-material compliant mechanisms with a Sequential Element Rejection and Admission method

Abstract: The design of multi-material compliant mechanisms by means of a multi Sequential Element Rejection and Admission (SERA) method is presented in this work. The SERA procedure was successfully applied to the design of single-material compliant mechanisms. The main feature is that the method allows material to flow between different material models. Separate criteria for the rejection and admission of elements allow material to redistribute between the pre-defined material models and efficiently achieve the optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Additionally, from Figure , it can be found that a localized strong material area appears on the compliant member, even though it is enclosed entirely by the weak material. This agrees well with the designs in the works about multi‐material topology optimization of compliant mechanisms …”
Section: Numerical Examplessupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, from Figure , it can be found that a localized strong material area appears on the compliant member, even though it is enclosed entirely by the weak material. This agrees well with the designs in the works about multi‐material topology optimization of compliant mechanisms …”
Section: Numerical Examplessupporting
confidence: 90%
“…In their work, the color‐level set method is employed to represent the multi‐material phases, and the objective is to maximize the mechanical advantage subject to the volume and input displacement constraints. The topology design of multi‐material compliant mechanisms by the multiple Sequential Element Rejection and Admission (SERA) method is presented in the work by Alonso et al The optimization is conducted to maximize the mutual potential energy subject to M constraints on the target volume fraction of the M materials. A bi‐level hierarchical optimization method is introduced to address the multi‐material design of compliant mechanisms in the work by Wang et al The hierarchical optimization develops decomposition approaches allowing the original complex multi‐material optimization problem to be reduced to a set of low‐order single‐material optimization sub‐problems.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum value of compliance,C, is equal to the compliance of the initial design where all element densities are equal toM, and x 1 = 1 (for the FGM problems). The third constraint is on the max local stresses in m regions as defined in (16), where m = 4 and m = 5 for the gripper and inverter designs respectively. Note that different m values were used for the convenience of having the same number of elements in each region -as the two problems had a different number of elements in their finite element mesh, we sought values of m such that N e is divisible by m and 4 ≤ m ≤ 8.…”
Section: Compliant Mechanismsmentioning
confidence: 99%
“…Yin et al [18] used a density based peak function interpolation which requires only one design variable per element. Wang et al and Alonso et al implemented a level-set method [19] and a SERA method [16], respectively which were both applied to multi-material compliant mechanism designs. By using multiple materials it is possible to reduce stress concentrations, however when discrete materials are used a stress concentration can be produced across the interface between materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al [7] used a peak function method to design multi-material compliant mechanisms. Alonso et al [8] adopted the sequential element rejection and admission method to produce compliant mechanism with multiple materials. Gaynor et al [9] proposed a topological design and fabrication process for multiple materials compliant structures.…”
Section: Introductionmentioning
confidence: 99%